Influence of cavitation, pelleting, extrusion and torrefaction petreatments on anaerobic biodegradability of barley straw and vine shoots. (February 2022) - Hidalgo, D.; Martín-Marroquín, J.M.; Castro, J.; Gómez, M.; Garrote, L.
Abstract: When dealing with lignocellulosic biomass in anaerobic digestion, a pretreatment stage is always required to open the structure of the material, facilitating its degradation. Numerous methods have been developed to pretreat lignocellulosic biomass. Four of them: cavitation, pelleting, extrusion and torrefaction have been comparatively studied in this paper as ways to improve the production of methane by anaerobic digestion of two different feedstocks: barley straw and vine shoots. Additionally, how the selected pretreatments and the nature of the feedstock influence the formation of individual volatile fatty acids was examined. Cavitation was revealed as the most efficient pretreatment, increasing 240% and 360% the methane production for barley straw and vine shoots, respectively, although in absolute terms, barley straw has higher production rate and yield than vine shoots. Torrefaction carried out at 180 °C increased methane production, 81% for straw and 25% for vine shoots, while the process at higher temperatures (220 °C) negatively affected biogas production from both feedstocks. Finally, volatile fatty acids accumulation seems to neutralize any potential positive effects of densification pretreatments. Graphical abstract: Image 1 Highlights: Cavitation, pelleting, extrusion and torrefaction are potential biomass pretreatments. Pretreatment led to breakdown of the robust structure of the biomass. Cavitation was the most efficient pretreatment, increasing up to 360% CH4 production. Torrefaction at 180 °C increased CH4 production 81% for straw and 25% for vine shoots. VFA accumulation neutralizes potential positive effects of densification pretreatment.